Út a Forráshoz. Az imádság természetrajza - SZABÓNÉ LÁSZLÓ, Lilla (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The Path to the Source: The Natural History of Prayer. In today’s fast-paced world, mental strain has become increasingly prevalent as a consequence of the constant use of digital devices. Within this context, it has become progressively more difficult to preserve or to establish the framework necessary for a life of prayer. This study seeks to rediscover the path leading back to the Source of our lives by exploring the nature and meaning of prayer. The paper examines both the phenomenology and theology of prayer, distinguishing between two contrasting attitudes: one in which a person attempts to exercise power over God and another in which the individual willingly submits to the power of God. The Bible and Christian theology bear witness to the rich diversity of prayer, often explained by authors through the lines of the Heavenly Father. Richard Foster identifies three movements of prayer: moving inward – seeking the transformation we need; moving upward – seeking the intimacy we long for; moving outward – seeking the ministry to which we are called. Reflecting on the practice of God’s presence, the study also considers the significance and interpretation of revelation. While the Bible remains the ultimate measure of all revelation, it is essential to recognize that God may manifest His presence in various ways. Finally, by engaging with the classical steps of Lectio Divina, the paper explores practical dimensions of renewing the life of prayer: cultivating silence, reading the Scripture, meditating on the Word, contemplating in God’s presence, and embodying divine truth through acts of service – thus, participating in the incarnational movement to which God invites us in prayer.